A Study of Social Media Addiction among Students from Higher Education Institutions - Parveen, Shahida; Singh, Kundan; Sagar, Pratibha (JOURNAL OF INDIAN EDUCATION, 2020)
The broad use of social sites or social media networking has been on the rise among the new generation students. In modern world, life cannot be imagined without Facebook, YouTube, WhatsApp, Instagram, LinkedIn, Twitter and other social media sites. Social media has made a promise to set up connections among people with its existence. Nowadays, many research studies have been investigated that social media is appearing anti-social, because social activities and engagement of students with society is decreasing day by day. To administer the present study, 200 students have been selected by purposive sampling, studied in Mahatama Jyotiba Fule Rohilkhand University, Bareilly in Uttar Pradesh (India). Data was collected through self-made tool named ‘Social Media Scale.’ Collected data was analysed with percentage method. This paper was an attempt to analyse the pattern of social networking usage and negative impact of social media on students. Results of the study showed that over use of social media is creating many health, social and learning outcome related issues among students of higher educational institutions.